The stylistic synthesis in the image of Peter I: Gavrila Derzhavin’s poetry - Васильев, Сергей (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article analyses the image of the first Russian Emperor created in Gavrila Derzhavin’s poetry, from the early poems of the 1770s to the late works written during the Patriotic War of 1812. Only some of the poems directly address Peter and his epoch. Mostly, the image of Peter I is auxiliary and in terms of the correlation of image and idea – usually emblematic. References to the tsar often correlate with reconstructing the stylistic context of Mikhail Lomonosov’s poetry, with continuing the formation of a special literary mythology, which presents Peter as a demiurge who created New Russia, and Catherine II as a continuator of his work, sometimes even surpassing her great predecessor in her achievements. In terms of genre, Derzhavin’s works which feature the image of Peter or include stylistically significant references to him, in some cases tend towards the synthesis of arts: musicality (hymn, ode) or ekphrasis. In creating the image of Peter I, the poet relies on the Western European context but also on generic and stylistic achievements of Old Russian literature. Special attention is paid to the poem “On the Prophecy of Simeon of Polotsk and Dmitry of Rostov at the Birth of Peter the Great”, which has not attracted the attention of literary scholars so far.